Estudio de la Gestión Productiva de la Asociación de Productores y Comercializadores de vino de Quinticusig del año 2016. Propuesta de un Manual de Procesos. - Albán Taipe, Paulina Salome (2017)
The elaboration of blue-berry wine involves a series of processes which go from the requirement of the fresh material to the commercialization. Nowadays, several organizations dedicated to this business use methods and strategies with a traditional vision, which causes problems. Now to know and attend the productive deficiencies, establish an adequate coordination of workflows and achieve the established production goals. The objectives of this researching were evaluate the process of production of blue-berry wine in the year 2016, of the Association of Producers and Marketers of Quinticusig, in order to know its limitations and strengths, and design a process manual as guide to the development of the activities in the production stage. To development to this research, was applied the descriptive method, the data was obtained from the checklist tool which was applied to the administrator and the operational staff of the Association. The methodology applied for the identification of processes was Business Process Management and the used tools for modeling process were Bizagi Modeler and Vensim. As a result of this work, was identified, analyze and model of the processes of production, in order to correct the existent processes, establish strategies that generate a benefit and finally, get and improve in the management of the organization. It is concluded that the research project developed is feasible and responds to a methodology to generate a new definition of production roles according to the workflow.